Perception of Islamic Religious Education Teachers Towards the Change of the 2013 Curriculum to an Independent Curriculum - Asy’ari, Muhammad Ma’ruf; M.Z, Riza Arif; Zuhriyah, Indah Aminatuz (Proceeding of International Conference on Islamic Education (ICIED); Vol 9 No 1 (2024): Proceeding of International Conference on Islamic Education (ICIED), 2024)
The change of curriculum from the 2013 curriculum to the independent curriculum has caused many problems in the field where many teachers are confused and do not fully understand the independent curriculum so that they are not ready to carry out learning using the independent curriculum. The unpreparedness is influenced by their perception of the independent curriculum launched by the government. This study is focused on finding out the perception of PAI teachers on the change of curriculum from the 2013 curriculum to the independent curriculum based on the aspects of changes in learning plan making, teaching and learning processes, lesson hours, and assessments in order to take generalizations related to the independent curriculum whether it can be well accepted or not. Literature study is the method used in this study and is analyzed using content analysis techniques. The results of the study explained that the perception of PAI teachers towards the change of curriculum from the 2013 curriculum to the independent curriculum based on the aspects of changes in learning plan making, teaching and learning processes, lesson hours, and assessments was perceived positively so that the implementation of the independent curriculum could be well accepted by all circles.